A sílaba cvc e sua função no sistema - Aquino, Carla de (2014)
This research was developed into the domain of linguistic theory and analysis, more specifically phonological studies, and aims at diferenciating light and heavy syllables in Portuguese. Quantity sensitive languages treat these two structures differently in relation to their role in processes such as stress assignment, tone, etc (GORDON, 2004). Tone or stress are rather assigned to heavy or bimoraic syllables (HYMAN, [1985] 2003; HAYES, 1989). Under this view, this research describes the behavior of CVC, which can be heavy in Portuguese, in the absence of long vowels, based on the process of stress assignment, a classical theme in the studies on phonological theory. Studies about stress in Portuguese meet no consensus on the role of weight for stress (CAMARA JR., 2007 [1970]; BISOL, 1992, 1994a; LEE, 1994; WETZELS, 1996, 2002, 2003, 2006; MAGALHÃES, 2004, 2010). The notion of contextually-dependent weight is necessary to describe stress, as in this work we treat weight as a relevant factor only at the right edge of the word (BISOL, 1992, 1994a; MAGALHÃES, 2004, 2010). Non-derived and derived items ended in CVC, in which final C is a sonorant [l,r,N] and the obstruent [S], compose the corpus of the study. They are all part of a 10.191 closed-syllable-word corpus. Once word final CVC usually behaves as strong, attracting main stress, we look for morphological reasons to justify the behavior of the exceptions. Thus, we argue that feet are constructed based on moras and that the stress rule in Portuguese is sensitive to the morphological structure of words, blocking weigth assignment to the terminal element in syllables which belong to specific morphemes. The analysis of the phonology/morphology interface in derived and non-derived items follows Pater (2000, 2004, 2007, 2009), counting on indexed constraints and considering inconsistencies as morphologically conditioned. Moreover, the dubious behavior of post-vocalic /S/, which is sometimes light, sometimes heavy, is as well discussed. Sonority constraints on moraic segments are verified (ZEC, 1998,1995, 2007). Optimality Theory, an output oriented model, which does not deal with rule ordering or derivation cycles, allows us to work with syllabification, weight and stress assignment in parallel.